PENINGKATAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MENGGUNAKAN BOLA SPONS - Harahap, Hasan Ashari (Universitas Tanjungpura, 2022)
The Problem in this study is whether there is an increase in Volleyball Bottom Passing Learning Outcomes Using Sponge Ball Class VIIA SMPN 4 Sungai Raya, Kubu Raya Regency for the Academic Year 2021-2022. The method used in this research uses a classroom action research approach because to improve the learning process through a cycle that includes planning, implementation, observation and reflection, it shows that in the first cycle the percentage of students